Brucellosis associated with stillbirth in a bottlenose dolphin in Australia. Issue 3 (6th February 2020) - Mackie, JT; Blyde, D; Harris, L; Roe, WD; Keyburn, AL
Abstract : A captive adult female bottlenose dolphin presented with stillbirth. The placenta appeared oedematous. No other gross lesions were evident in the placenta or the stillborn calf. Histopathology revealed mild multifocal placentitis and foetal encephalitis. Brucella sp. was isolated from lung, liver, spleen and kidney. Sequence and phylogenetic analysis demonstrated this organism to be most similar to Brucella ceti sequence type (ST) 27. Brucella sp. DNA was detected in formalin‐fixed paraffin‐embedded placenta and brain by real‐time PCR using primers targeting the IS 711 gene. Immunohistochemical staining revealed Brucella sp. antigen in placental inflammation. This is the first report of isolation of Brucella sp. from a marine mammal in the Southern Hemisphere and the first report of marine Brucella ‐associated disease in Australia.